K336I mutant actin alters the structure of neighbouring protomers in filaments and reduces affinity for actin-binding proteins - Umeki, Nobuhisa (Sci Rep, 2019)
Mutation of the Lys-336 residue of actin to Ile (K336I) or Asp (K336E) causes congenital myopathy. To understand the effect of this mutation on the function of actin filaments and gain insight into the mechanism of disease onset, we prepared and biochemically characterised K336I mutant actin from Dictyostelium discoideum. Subtilisin cleavage assays revealed that the structure of the DNase-I binding loop (D-loop) of monomeric K336I actin, which would face the adjacent actin-protomer in filaments, differed from that of wild type (WT) actin. Although K336I actin underwent normal salt-dependent reversible polymerisation and formed apparently normal filaments, interactions of K336I filaments with alpha-actinin, myosin II, and cofilin were disrupted. Furthermore, co-filaments of K336I and WT actins also exhibited abnormal interactions with cofilin, implying that K336I actin altered the structure of the neighbouring WT actin protomers such that interaction between cofilin and the WT actin protomers was prevented. We speculate that disruption of the interactions between co-filaments and actin-binding proteins is the primary reason why the K336I mutation induces muscle disease in a dominant fashion.